Effect of Feed Texture on Growth Performance and Litter Moisture When Fed to Growing-Finishing Commercial Toms - Roberson, Kevin D. (International Journal of Poultry Science, 2003)
Large White male turkeys were fed diets with similar nutrient content using either a corn-soybean meal-wheat middlings based diet fed as pellets or mash or a corn-soybean meal based mash diet. The pelleted diets were processed either with or without a commercial pellet binder. Each treatment was assigned to four pens of 25 toms from 6 to 18 wk of age. Body weight and feed consumption were determined at 21 d intervals during the trial. Turkeys fed pelleted diets were heavier at 9 and 12 wk of age only. However, this effect was due to reduced growth performance of birds fed the corn-soybean meal mash diet which had less energy from added fat compared to the other diets. Cumulative feed conversion (feed:gain) was improved when pelleted diets were fed throughout the trial. Pellet quality was fair up to 12 wk of age and poor during the latter part of the study when high added fat was included in the diets. Litter moisture was increased at the end of the trial when pelleted diets were fed. However, leg problems were not evident in this study.